Cultural and Social Bias Leading to Prenatal Sex Selection: India Perspective - Chakravarty, Nayan; Dabla, Vandana; Sagar, Moni; Neogi, Sharmila; Markan, Mridu; Segan, Mehak; Agnani, Shilpi; Kapahi, Pooja; Neogi, Sourav (Frontiers in Global Women's Health, 2022)
Globally, the 23.1 million missing female births have been documented, resulting in an imbalanced Sex Ratio at Birth (SRB) between late nineteens till 2017; with India accounting for almost half of this missing women population. While country is progressively taking measures to enhance women’s position in the society and implementing policies towards augmenting the value of girl child; some deep rooted cultural and social beliefs propel strong son preference, resulting in active daughter discrimination. The continuance of patriarchal norms and inequitable gender roles, resulting in son preference, fertility decrease and lowering family size preferences, and technical breakthroughs that allow for the identification of the sex of the foetus, are all connected to distortions in the sex ratio at birth. Son preference is a well-documented phenomenon in India, and its implications for skewed gender ratios, female feticide, and higher child mortality rates for girls have piqued researchers' and policymakers' interest. The fundamental factors of son preference as an ideology are less widely investigated. With this objective, an extensive secondary review was conducted of the socio-cultural norms and biases leading to increased prenatal sex selection in India, despite being available laws against it. The study findings suggest that it is imperative to imply consistent and collective efforts of all the stakeholders. Changing the value of girls requires collective effort and an equal participation of all stakeholders, including civil society organisations and local community.